Antioxidative and Antiapoptotic Effects of Delta-Opioid Peptide [D-Ala2, D-Leu5] Enkephalin on Spinal Cord Ischemia-Reperfusion Injury in Rabbits - Fu, Danyun; Liu, Haitong; Li, Shitong; Chen, Lianhua; Yao, Junyan (Frontiers in Neuroscience, 2017)
Background: In our previous study, we found that regional administration of delta-opioid peptide [D-Ala2,D-Leu5] enkephalin (DADLE) could provide dose-dependent protection on spinal cord ischemia-reperfusion (I/R) injury in rabbits. However, the relative protective molecular mechanisms underlying this neuroprotection remain unclear. The purpose of this study was to investigate whether DADLE provided the protection in spinal cord I/R injury through its antioxidant property by decreasing malondialdehyde (MDA) and nitric oxide (NO) levels and increasing glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) levels and through its antiapoptotic capacity by inhibiting caspase-3 and p53 expression. Methods: The rabbits were divided into three groups. The animals in Group NS and Group DADLE were administered with normal saline (NS) or DADLE via aorta during 30 min of ischemia respectively, while the one in Group Sham received no intervention. During the period of reperfusion, the rabbit’s blood samples were collected for enzyme-linked immunoabsorbent assay (ELISA) examinations of MDA, NO, GSH-Px and SOD. At 48 h after reperfusion, the lumbar spinal cords were harvested for immunohistochemical, real-time polymerase chain reaction (PCR) and western blot studies to detect the caspase-3 and p53 expressions. Results: The activities of serum MDA and NO showed significant reductions in the DADLE group as compared with the control group. By contrast, the levels of serum GSH-Px and SOD were significantly higher in the DADLE group than those in the NS group. In addition, caspase-3 and p53 expression were significantly increased in the NS group, while DADLE mitigated these changes. Conclusions: The protective effects of DADLE at the dosage of 0.05 mg/kg may be related to its antioxidant and antiapoptosis properties in the rabbit model of spinal cord I/R injury.